Brief research report: Repurposing pentoxifylline to treat intense acute swimming-Induced delayed-onset muscle soreness in mice: Targeting peripheral and spinal cord nociceptive mechanisms - Sergio M. Borghi; Sergio M. Borghi; Tiago H. Zaninelli; Telma Saraiva-Santos; Mariana M. Bertozzi; Renato D. R. Cardoso; Thacyana T. Carvalho; Camila R. Ferraz; Doumit Camilios-Neto; Fernando Q. Cunha; Thiago M. Cunha; Felipe A. Pinho-Ribeiro; et al. (Frontiers Media S.A., 2023)
In this study, we pursue determining the effect of pentoxifylline (Ptx) in delayed-onset muscle soreness (DOMS) triggered by exposing untrained mice to intense acute swimming exercise (120 min), which, to our knowledge, has not been investigated. Ptx treatment (1.5, 4.5, and 13.5 mg/kg; i.p., 30 min before and 12 h after the session) reduced intense acute swimming-induced mechanical hyperalgesia in a dose-dependent manner. The selected dose of Ptx (4.5 mg/kg) inhibited recruitment of neutrophils to the muscle tissue, oxidative stress, and both pro- and anti-inflammatory cytokine production in the soleus muscle and spinal cord. Furthermore, Ptx treatment also reduced spinal cord glial cell activation. In conclusion, Ptx reduces pain by targeting peripheral and spinal cord mechanisms of DOMS.